A review of airport runway capacity evaluation model. Issue 7 (March 2020) - Lei, Jichao; Chong, Xiaolei; Chen, Dongfang; Chen, Zhenglei; Chen, Qiqi
Abstract: In this paper, we analyze the domestic scholars about the airport runway capacity evaluation model, and they are mainly the analysis and introduction of some commonly used runway capacity evaluation methods and specific runway capacity evaluation models. These models respectively include the takeoff and landing capacity of aircraft, and give the calculation methods of runway capacity in various cases. By seeking the similarities and differences of these evaluation models, the future research focus and direction are put forward.